Learning curve of full-endoscopic lumbar discectomy - Hsu, Hsien-Ta (Springer-Verlag, 2012)
PURPOSE: To report the learning curve of full-endoscopic lumbar discectomy for a surgeon naive to endoscopic surgery but trained in open microdiscectomy. METHODS: From July 2006 to July 2009, 57 patients underwent full-endoscopic lumbar discectomy and 66 underwent open microdiscectomy. The clinical results were evaluated with a visual analog scale (VAS) and the Oswestry Disability Index (ODI). Spearman’s coefficient of rank correlation (rho) was used to assess the learning curves for the transforaminal and interlaminar procedures of full-endoscopic lumbar discectomy. RESULTS: After full-endoscopic lumbar discectomy, the VAS and ODI results of the patients followed up were comparable with those of open microdiscectomy. A steep learning curve was observed for the transforaminal procedure, but not the interlaminar procedure. CONCLUSIONS: The learning curve of the transforaminal approach was steep and easy to learn, while the learning curve of the interlaminar approach was flat and hard to master.